2011
DOI: 10.4103/0019-5359.109259
|View full text |Cite
|
Sign up to set email alerts
|

Anti-microbial resistance profile of Citrobacter species in a tertiary care hospital of southern India

Abstract: Citrobacter isolates resistant to multiple anti-microbial agents have emerged, including strains resistant to imipenem, making it an emerging nosocomial pathogen. Therefore, the results of this study suggest that surveillance of anti-microbial resistance in Citrobacter is necessary. Antibiotic policy should be formulated in the hospital. Depending on the antibiotic sensitivity pattern of the Citrobacter isolates, antibiotics should be used, and proper infection control measures should be strictly followed to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
3
11
0
Order By: Relevance
“…Susceptibility to Amikacin was 87.69% but study conducted by (Gandam Pavani;2012) showed 100% susceptibility to Amikacin in contrast (K Ashish et al; 2012) showed only 25% susceptibility to Amikacin. Most effective agent against Citrobacter species was found to be Imipenem (90.76% sensitivity) followed by Cefoperazone-Sulbactam (89.23%sensitivite) when compared with other study where most effective drug was found to be Imipenem (91.8% sensitive) followed by Piperacillin-Tazobactam (58.3% sensitive) (Metri BC et al;2011). To conclude, we would like to bring notice to the fact that Citrobacter though not uncommon isolate is increasing with its multi-drug resistance and Extended Beta -lactamase producers.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Susceptibility to Amikacin was 87.69% but study conducted by (Gandam Pavani;2012) showed 100% susceptibility to Amikacin in contrast (K Ashish et al; 2012) showed only 25% susceptibility to Amikacin. Most effective agent against Citrobacter species was found to be Imipenem (90.76% sensitivity) followed by Cefoperazone-Sulbactam (89.23%sensitivite) when compared with other study where most effective drug was found to be Imipenem (91.8% sensitive) followed by Piperacillin-Tazobactam (58.3% sensitive) (Metri BC et al;2011). To conclude, we would like to bring notice to the fact that Citrobacter though not uncommon isolate is increasing with its multi-drug resistance and Extended Beta -lactamase producers.…”
Section: Discussionmentioning
confidence: 62%
“…The genus Citrobacter is a distinct group of aerobic Gramnegative bacilli from the Enterobacteriaceae family (Najar M.S et al; 2009). It is an opportunistic pathogen that can cause diarrhea, septicemia, meningitis, and urinary tract and respiratory system infection (Metri BC et al;2011). Citrobacter isolates were found to be the third most common organism causing UTI in hospitalized patients after Escherichia coli and Klebsiella species accounting to 9.4% of all isolates (Lipsky BA et al;1980).…”
Section: Introductionmentioning
confidence: 99%
“…Majority of isolates were recovered from pus 38%, urine 25%, sputum 17% as reported by Basavaraj et al pus 48%, urine 24%, sputum20%. 3 Citrobacter koseri was commonly isolated from urine sample from critically ill and debilitated patients suggesting chronic urinary catheter related infections as seen in Ranjan et al 4 Antibiotic susceptibility pattern showed sensitivity to Carbapenems (98% 7,8 The AmpC producers among Citrobacter species was 30% as compared to Mehar Rizvi 29%. 7 In this study, maximum sensitivity was observed with Imipenem 98% as compared with other studies, but this drug should not be used indiscriminately and should be kept as reserve drug as otherwise resistance to this drug may cause a threat to treatment.…”
Section: Discussionmentioning
confidence: 98%
“…1,2,3 Although, Citrobacter spp. are infrequent nosocomial pathogens, a local or systemic breech in the host defence can allow them to cause a range of infections.…”
Section: Introductionmentioning
confidence: 99%
“…The genus of Citrobacter comprised 11 different species, among which C. freundii is the most prevalent found in infections. C. freundii is associated with opportunistic nosocomial infections such as Urinary Tract Infections (UTIs), wound infections, gastrointestinal diseases, septicemia, and meningitis, especially in immunecompromised patients [6][7][8]. Although rare in newborns, Citrobacter infection usually leads to meningitis and intracranial abscesses that in 75% of patients with meningitis associates with a high rate of mortality and morbidity [5,9,10].…”
Section: Introductionmentioning
confidence: 99%